Primary CNS lymphoma commonly expresses immune response biomarkers. Issue 1 (19th February 2020) - Ou, Alexander; Sumrall, Ashley; Phuphanich, Surasak; Spetzler, David; Gatalica, Zoran; Xiu, Joanne; Michelhaugh, Sharon; Brenner, Andrew; Pandey, Manjari; Kesari, Santosh; Korn, W Michael; Mittal, Sandeep; et al.
Abstract: Background: Primary central nervous system lymphoma (PCNSL) is rare and there is limited genomic and immunological information available. Incidental clinical and radiographic responses have been reported in PCNSL patients treated with immune checkpoint inhibitors. Materials and Methods: To genetically characterize and ascertain if the majority of PCNSL patients may potentially benefit from immune checkpoint inhibitors, we profiled 48 subjects with PCNSL from 2013 to 2018 with (1) next-generation sequencing to detect mutations, gene amplifications, and microsatellite instability (MSI); (2) RNA sequencing to detect gene fusions; and (3) immunohistochemistry to ascertain PD-1 and PD-L1 expression. Tumor mutational burden (TMB) was calculated using somatic nonsynonymous missense mutations. Results: High PD-L1 expression (>5% staining) was seen in 18 patients (37.5%), and intermediate expression (1–5% staining) was noted in 14 patients (29.2%). Sixteen patients (33.3%) lacked PD-L1 expression. PD-1 expression (>1 cell/high-power field) was seen in 12/14 tumors (85.7%), uncorrelated with PD-L1 expression. TMB of greater than or equal to 5 mutations per megabase (mt/Mb) occurred in 41/42 tumors, with 19% ( n = 8) exhibiting high TMB (≥17 mt/Mb), 71.4% ( n = 30) exhibiting intermediate TMB (7–16 mt/Mb), and 9.5% ( n = 4) exhibiting low TMB (≤6 mt/Mb). No samples had MSI. Twenty-six genes showed mutations, most frequently in MYD88 (34/42, 81%), CD79B (23/42, 55%), and PIM1 (23/42, 55%). Among 7 cases tested with RNA sequencing, an ETV6-IGH fusion was found. Overall, 18/48 samples expressed high PD-L1 and 38/42 samples expressed intermediate to high TMB. Conclusions: Based on TMB biomarker expression, over 90% of PCNSL patients may benefit from the use of immune checkpoint inhibitors.